Mastering IDEAScript : the definitive guide - Mueller, John, 1958- (Hoboken, NJ : Wiley, 2011)
With approximately 44,000 users in the U.S. and Canada, as well as 42,000 in Europe, IDEA software has become a leading provider of data analysis software for use by auditors and accountants. Written to provide users with a quick access guide for optimal use of IDEAScript, Mastering IDEAScript: The Definitive Guide is IDEA's official guide to mastering IDEAScript, covering essential topics such as Introducing IDEAScript, Understanding the Basics of IDEAScript Editor, Designing Structured Applications, Understanding IDEA Databases and much more. For auditors, accountants and controllers.
Introducing IDEAScript -- Creating Your First IDEAScript Application -- Understanding the Basics of the IDEAScript Editor -- Designing Structured Applications -- Working with Data -- Using Conditional Statements and Loops -- Understanding IDEA Databases -- Working with Databases -- Considering the CaseWare IDEA Object Model -- Performing Mathematical Tasks -- Interacting with Arrays -- Creating Interactive Dialog Boxes -- Locating Information in Databases -- Importing and Exporting Data -- Working with Files -- Working with Other Applications -- Performing Data Analysis Tasks -- Working with Charts and Graphs -- Defining Reports -- Considering Database Security -- Debugging Your Application -- Performing Project Management Tasks -- Converting Visual Script to IDEAScript.
Print version record.
Keywords: Auditing -- Data processing; Accounting -- Data processing; Scripting languages (Computer science); Data structures (Computer science); Business; Computer science; BUSINESS & ECONOMICS -- Accounting -- Financial; Accounting -- Data processing; Auditing -- Data processing; Data structures (Computer science); Scripting languages (Computer science); Electronic books